Polícia Nas Encruzilhadas: Macumbas, Macumbeiros E Ordem Social (1930 - 1950) - Santos, Marcos Paulo Amorim Dos [UNIFESP] (2017)
This dissertation aims to reflect over the actions of the São Paulo Police between the years 1930-1950 in the fight, chase by “macumbas” and “macumbeiros”, as the police definition. To search for this problem, we use press articles, Civil Police reports and process in this period. Through these documents, we want to investigate how the movements of the civil police were in line with Brazilian state issues in the cut period, reflecting, finally, as “macumbas” and “macumbeiros” represented risks to the utopia of modernity and ongoing progress in the Vargas Period.